Gloss to the Judgment of the Court of Justice of the European Union (Third Chamber) of 25 November 2021 in Case C‑488/20, Delfarma SP. Z o.o. v. Prezes Urzędu Rejestracji Produktów Leczniczych, Wyrobów Medycznych i Produktów Biobójczych - Mełgieś, Katarzyna Małgorzata (Review of European and Comparative Law, 2023)
Medicinal products are a special type of goods due to their importance for human health and life, and their trade is generally under the scope of Directive 2001/83/EC of the European Parliament and of the Council of 6 November 2001 on the Community code relating to medicinal products for human use. The preamble to this act states that the essential aim of the rules governing the production, distribution and use of medicinal products must be to safeguard public health. Hence, in the above-mentioned directive, the rules related to the authorisation of medicinal products for marketing and pharmacovigilance are very important. At the same time, it should be noted that parallel import of medicinal products as a form of trade in an EU Member State in connection with their authorisation for marketing in another Member State, although it has a long tradition, has not had a clear normative pattern, and has not been subject to the scope of Directive 2001/83/EC. It is based on the achievements of the acquis communautaire developed in this area and the principle of free movement of goods (Article 34 TFEU) and its exceptions set out in Article 36 TFEU concerning the protection of human health and life. The commented judgment sets an example of one more verdict confirming the interpretation of Articles 34 and 36 TFEU, according to which national provisions of a Member State should be considered unacceptable, according to which the withdrawal of the marketing authorisation for the reference medicinal product in the country of import has the automatic effect of expiring the parallel import authorisation. At the same time, new circumstances affecting the safety of the medicinal product on the market were analysed to give the conclusion as declared in the sentence.